The level of awareness of string from the Faculty of Music UiTM pertaining the time keeping skills and methods when playing in a string quartet / Sharifah Nadhirah Syed Faiz Binyahya - Syed Faiz Binyahya, Sharifah Nadhirah (2012)
This study was conducted as to investigate the level of awareness of string student from the Faculty of Music UiTM pertaining the time keeping skills and methods when playing in an ensemble in this case in a string quartet. A set of 3 part interview question was design to gain the primary data of this study. The data were collected by interviewing 4 violin student, 2 viola students and 4 cello students from different department of the Faculty of music UiTM. After the interview session there is an observation where to really understand and see whether what the respondents answered during the interview they really doing it in rehearsals. The overall finding of this study indicates that the students were aware on the fundamentals of playing in a string quartet; however 70% of the students student were not aware how their instrument sound projection ability to speaks. Each student has their own way of awareness and methods when playing in a string quartet. A suggestion had been made to conduct the same study to the general students of the Music Faculty in UiTM inclusive of all instruments to find out the differences in methods and their awareness in this matter